Manfaat Pelatihan Akuntansi Dalam Meningkatkan Cakupan Penggunaan Informasi Akuntansi Oleh Koperasi (Suatu Riset Eksperimental) - Sungkono Sungkono (Sekolah Tinggi Ilmu Ekonomi Bisnis dan Perbankan, 2011)
Accounting activities produces the accounting information where its give a benefit to users for business decision-making. But in fact, accounting has not played an important role in the activities of small and medium enterprises. Accounting information has not been utilized optimally by the actors in the field of small and medium enterprises, including cooperatives. To be useful for accounting activities they will need to be strategic steps in order to raise awareness of the perpetrators cooperatives, increase knowledge, and skills in accounting, so that they realize the importance of accounting in their businesses. Training coupled with guidance is one solution to raise awareness, increase knowledge, and skills of managers and employees of cooperatives, so that the program is expected to accounting information generated more quality and useful in their business decision making. By experimental research that taking subjects as many as 30 pieces of existing cooperatives in the district of Bantul as samples, researcher find empirical evidence there is a significant in the extent of usage accounting information between experiment group and control group. It can be concluded that training in the field of accounting has benefits in increasing the extent of usage of accounting information in decision making by the cooperative.